Effect of early postnatal supplementation of newborns with probiotic strain E. coli O83:K24:H31 on allergy incidence, dendritic cells, and microbiota - Súkeníková, Lenka; Černý, Viktor; Thon, Tomáš; Roubalová, Radka; Jirásková Zákostelská, Zuzana; Novotná, Olga; Petrásková, Petra; Boráková, Kristýna; Kocourková, Ingrid; Lodinová-Žádníková, Rája; Musil, Zdeněk; Kolářová, Libuše; et al. (Frontiers in Immunology, 2023)
Probiotic administration seems to be a rational approach to promote maturation of the neonatal immune system. Mutual interaction of microbiota with the host immune system is critical for the setting of appropriate immune responses including tolerogenic one and maintenance of the homeostasis. On the other hand, our knowledge of the modes of actions of probiotics is still scarce. In our study, probiotic strain Escherichia coli O83:K24:H31 (EcO83) was administered to neonates of allergic mothers (AM, neonates with increased risk for allergy development) within 48 hours after the delivery and the impact of this early postnatal supplementation on allergy incidence and selected immune markers has been analyzed 10 years after the primary EcO83 administration. We have observed decreased allergy incidence in ten-year-old children supplemented by EcO83 (13 of 52 children were allergic) in comparison with non-supplemented children of AM (16 of 42 children were allergic). The early postnatal EcO83 supplementation appeared to limit the allergy in the high risk group (children of allergic mothers) to the low risk group (children of healthy mothers). Dendritic cells (DC) in the peripheral blood of EcO83 supplemented children do not differ significantly in cell surface presence of CD83. Immunomodulatory capacity of EcO83 on dendritic cells was tested in vitro as well. Both directly isolated myeloid and in vitro monocyte derived DC from cord blood increased CD83 expression together with IL-10 secretion after EcO83 stimulation. The effect of early postnatal EcO83 supplement on microbiota composition of the ten year old children was characterized by next generation sequencing and we have not observed significant changes in microbiota composition of EcO83 supplemented and non-supplemented children at the age of ten years. Early postnatal EcO83 supplementation appears to lower allergy incidence in children of AM. It seems that the beneficial effect of EcO83 is mediated via modulation of DC functional capacities without impacting microbiota composition. Larger scale studies will be necessary to confirm these preliminary findings.